Integration of Electricity Networks in the Arab World : Regional Market Structure and Design - World Bank (Washington, DC, 2014)
The Arab countries have enjoyed sustained economic growth in recent years, and the high economic growth has triggered a rapid increase in energy demand, particularly for electricity. Besides enabling energy imports, interconnected power networks impart a series of additional benefits such as improved system reliability, reduced reserve margins, reactive power support, and energy exchanges that take advantage of daily and seasonal demand diversity and disparities in marginal production costs. As a result, a world-class electricity supply system can be achieved with much lower capital expenditures and ongoing expenses than will otherwise be attainable on an individual-country basis. The regional power interconnection of the Gulf Cooperation Council (GCC), allows electricity exchange among its six member states: Kuwait, Saudi Arabia, Bahrain, Qatar, the United Arab Emirates (UAE), and Oman under an agreement signed in 2009. The interconnection is targeted at sharing capacity reserve and improving supply reliability, which will reduce the need for investment in new generation capacity. This study, which focuses on the development of the institutional and regulatory framework for electricity trade in the Arab world, is one of three currently being carried out by the League of Arab States (LAS) on the development of regional electricity markets (REMs): part one: study of interconnections of electrical systems in the Arab world; part two: study of electricity-gas trade among the Arab countries; and part three: study of institutional and regulatory frameworks. This study focuses on the institutional and regulatory aspects of cross-border trade and electricity market integration among the 22 LAS member countries, and between the Arab countries and potential neighboring markets. This study comprises two phases. Phase one, is main report (volume one), examines regional market structure and design. Phase two (volume 2) examines principles of market regulations and legal arrangements including a draft road map for a transition path toward market integration and governance documentation including drafts memorandum of understanding, general agreement, general pan Arab electricity market agreement, and regional grid code.